2011
DOI: 10.1007/s10608-011-9386-7
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic Moderators of the Effectiveness of Problem-Focused and Emotional-Approach Coping Interventions

Abstract: A prospective dyadic study examined whether supportive or unsupportive behaviors of a partner and individual differences in attention to emotion moderated the effectiveness of problem-focused and emotionalapproach coping interventions. At Time 1, dimensions of emotional experience were assessed using self-report. Several days later participants (two friends of the same gender) were randomly assigned to either a problemfocused or an emotional-approach coping intervention. Positive affect, negative affect, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Because the terminology of emotion‐focused coping can be misleading, Baker and Berenbaum () offer what they call emotional‐approach coping : ‘actively identifying, processing, and expressing one's emotions, thus providing information about the status of one's goals’ (p. 550). This language resonates more clearly with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Because the terminology of emotion‐focused coping can be misleading, Baker and Berenbaum () offer what they call emotional‐approach coping : ‘actively identifying, processing, and expressing one's emotions, thus providing information about the status of one's goals’ (p. 550). This language resonates more clearly with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The theory suggested that when encountering stress, individuals tend to choose between problem‐focused coping and emotion‐focused coping to help them alleviate psychological tension. The former refers to the tendency to take action to alter the source of a problem, whereas the latter refers to the tendency to reduce or eliminate emotional distress associated with a problem (Baker & Berenbaum, ). Although the objective of both types of coping is to help individuals reduce stress perception (Lazarus & Folkman, ), research has found that problem‐focused coping is more likely to produce positive outcomes because it allows people to completely eliminate the source of stress (Hsieh et al, ; Lewin & Sager, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other words, the lack of mindfulness, which happens as a result of social media addiction, will cause people to experience emotional exhaustion at work. Generally, emotional exhaustion is considered a cognitive process that happens when individuals perceive that they are unable to deal with job demands and stressful situations in the workplace (Baker & Berenbaum, ). Charoensukmongkol () suggested that mindfulness helps people become aware of their thoughts and feelings and maintain a non‐judgmental attitude towards what they are experiencing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research demonstrated that the three coping strategies often work in tandem; the regulation of anxiety and fear (emotion-focused coping) enables the person to focus on taking a decision (problem-focused coping), or the cognitive restructuring (problem-focused coping) can be guided by underlying values and goals (meaning-focused coping) [ 29 , 30 ]. In addition, different coping strategies appear to be beneficial depending on the particular situation and context, e.g., problem-focused coping was found to be predominantly helpful in high controllability situations, while emotion-focused coping was more effective under low controllability conditions [ 31 ].…”
Section: Introductionmentioning
confidence: 99%